2018
DOI: 10.24141/1/4/2/1
|View full text |Cite
|
Sign up to set email alerts
|

Stavovi studenata studija sestrinstva Zdravstvenog veleučilišta o sestrinstvu u Hrvatskoj

Abstract: Sestrinstvo je danas priznata profesija koju nitko ne osporava. Moderno sestrinstvo favorizira edukaciju kao prioritet u profesionalnom životu medicinskih sestara. Više i visoko obrazovanje medicinskih sestara standard je u modernim državama. Uspješnost medicinske sestre ne ovisi samo o njezinoj humanosti i sposobnosti svladavanja suvremene tehnologije nego i o trajnoj edukaciji medicinskih sestara. Cilj ovoga istraživanja bio je istražiti kakvi su stavovi i mišljenja studenata svih godina preddiplomskog studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…A 2020 study of 300 nursing students in Saudi Arabia also revealed positive attitudes toward nursing as a profession (14). Similar results have been obtained through research in Croatia (5,15), Iraq (16), Saudi Arabia (17), Turkey (18), and Nepal (19).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…A 2020 study of 300 nursing students in Saudi Arabia also revealed positive attitudes toward nursing as a profession (14). Similar results have been obtained through research in Croatia (5,15), Iraq (16), Saudi Arabia (17), Turkey (18), and Nepal (19).…”
Section: Discussionsupporting
confidence: 83%
“…When nursing students begin their studies, they have attitudes and beliefs regarding nursing that change as students are influenced by the educational program (5). The final year of academic study is a turning point for nursing students, most of whom are aware of the nurse's professional role (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study conducted by Čukljek S. among first-year nursing students at the University of Applied Health Sciences of Zagreb indicates that the development of professional identity and perception of nursing is significantly influenced by the media, the environment and education (18).…”
Section: Discussionmentioning
confidence: 99%